FROM THE EDITOR = Redaksioneel - Lategan, Bernard C. (Scriptura, 1984)
The contributions to this issue formed part of a symposium organized by the department of Biblical Studies of the University of Stellenbosch on May 2 and 3 of this year under the general theme: A changed society from the perspective of Christian faith. The interest generated by the theme and the participation of the audience in the discussion was such that it was decided to make the papers and the reactions of the various respondents available to a wider public. They are published here (with minor alterations) in the same format as presented at the symposium.